Deaths by Covid-19 in the city of Crato-CE: Epidemiological profile (Research, Society and Development, 2022)
Objective: To describe the profile of deaths by Covid-19 in the city of Crato-CE, in order to identify which groups had greater complications in the clinical picture of the disease, reaching death. Methodology: This is a cross-sectional study, with a quantitative approach, carried out using secondary data. The territory under study is the Municipality of Crato-CE. Results: 225 deaths were analyzed from May 2020 to August 16, 2021, 40.88% were female, with a mean age of 70 years and 59.11% were males, with a mean age of 68 years. Regarding race/color, 59% were brown and 21% were not informed, 10.7% were white, 5.8% were black and 2.2% were yellow. Of the 225 deaths, 68% had some comorbidity. The neighborhoods that presented significant numbers of deaths were Seminario, Vila Alta, Muriti, Pinto madeira, Vila São Bento, Centro, and Ponta da Serra. Conclusion: The profile of deaths by Covid-19 in the city of Crato-CE is formed mostly by male patients, aged 60 years or older, brown and with the presence of comorbidities.